Development of Multimedia Based on Autodesk Inventor Software on the Concept of Relative Velocity to Increase Students Generic Science Skill - Ariyano Ariyano; Amay Suherman; Handiansyah Akhmadi (Journal of Vocational Education Studies, 2020)
This research aims to develop autodesk inventor-based multimedia that was designed to increase students generic science skill on the application of relative velocity at kinematics and dynamics courses. This study used the mini course method developed by Borg and Gall, including the stage of analysing and planning, developing early product, and validating from the expert and revision the early product. Based on the analysis conducted, it was revealed that there were five indicators that students had difficulties with, including illustrating kinematic diagram, illustrating velocity direction, calculating absolute velocity, illustrating velocity polygon, and calculating velocity based on velocity polygon. Those five indicators were related to six generic science aspects, including modelling, symbolic language, laws of causality, logical consistency, scale awareness, and observation. The developed multimedia consists of nine displays of slider-crank mechanism and eight displays of four-bar mechanisms, using .idw, .iam, and .mp4 formats and has been validated by material and media experts. Based on the judgment from the experts, the inventor-based multimedia was worthy to be applied in the course.